GOOD BAZNAS GOVERNANCE MODEL ON NATIONAL ZAKAT AGENCY (BADAN AMIL ZAKAT NASIONAL) IN SEMARANG CITY - Zainal Alim Adiwijaya; Suraya Ahmad; Edy Suprianto (ITB AAS Indonesia Surakarta, 2024)
Good governance is very important for companies to implement in order to gain the full trust of the community, including zakat institutions. Good governance of zakat management institutions is the hope of every community because one of the main goals of zakat is to provide benefits to all people. This study aims to analyze the governance of zakat management institutions from the accountability, transparency and fairness aspects. The sample selection technique used is purposive sampling, with the data collection technique chosen as a semi-structured interview and literature study. As for the interviews, data were collected by triangulation method (amil of zakat, scholars/experts, and muzakki). The results of interviews with informants were then carried out by cross-checking with the perspective of stakeholders, namely zakat experts and muzakki. Results of this study indicate that good governance of zakat management institutions does not only rely on the three indicators of accountability, transparency and fairness but there are other important things besides the three indicators, namely amanah. Trust from the community is very important because it can increase the amount of zakat collected. Therefore, it is necessary for BAZNAS to implement principles of accountability, financial reporting transparency, fairness, and trust. Keywords: Accountability; Amanah; BAZNAS; Fairness; Transparency